(untitled) (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2021)
God as Creator: the quest of the prehistoric Jesus The pre-existent Christ as agent of creation has had a profound influence on the early Christian worldview. This is reflected in the gospel according to St John, but also elsewhere in the New Testament (1 Corinthians 8:6, Colossians 1:15-20, Hebrews 1:1-3). Its evaluation as a core element of the Christian creed was confirmed by the councils of Nicaea and Constantinople. This doctrine of the prehistoric Jesus is problematic in the light of the scientific premise that the natural world is driven by random change and natural selection, which results in a dichotomy between the personalities of the historic and prehistoric Jesus or may sacrifice both. An alternative solution may be found in a re-appraisal of the compatibility of Biblical Theology and secular scientific theories of origin.